Untitled. - Jay, Martin; Flax, Jane (History & Theory, 1993)
Reviews the book `Postmodernism, or, the Cultural Logic of Late Capitalism,' by Fredric Jameson. Marxism's resistance to developments in critical and cultural theory; Postmodernism as late capitalism and completed modernity; Hegemony of spatialization over temporalization; Nominalism as the key to modernist aesthetics.